PENERAPAN KALIGRAFI JEPANG SEBAGAI METODE PEMBELAJARAN HURUF KANJI DASAR TERHADAP SISWA SMA KR. EBEN HAEZER MANADO (APPLICATION OF JAPANESE CALLIGRAPHY AS KANJI LETTER BASICS LEARNING METHOD TO STUDENTS OF SMA KR. EBEN HAEZER MANADO) - Tatiana Stary Claudia (Balai Bahasa Sulawesi Utara, 2016)
In general, the Japanese language learners are familiar with kanji, although these letters are difficult to learn. In this study, the researcher will look at the implementation of the method of Japanese calligraphy as a method of studying kanji. The application of it can improve the ability of learners to master Japanese kanji. This method enables students to engage directly of experience and training that will help them to learn it easily. The long term goal in using this method of Japanese calligraphy will be a learning method that can facilitate learners in learning kanji because much exercises done by learners will make that learning become more fun and easier. The application of calligraphy as a method of learning kanji to learners will be the goal of researcher in order to make this research be useful in increasing the motivation and the main attraction for the students to learn kanji. Then with learning kanji letters through the method of Japanese calligraphy will make them memorized longer by the learners.